Application of open port sampling interface mass spectrometry (OPSI‐MS) to deuterium exchange as an aid for structural elucidation. (8th February 2020) - Ray, Andrew D.; Clemens, Graeme; Holman, Stephen W.
Abstract : Rationale: Deuterium exchange has been demonstrated to provide additional information to accurate mass measurement and collision‐induced dissociation on unknown chemical structures. An enhanced method for rapid deuterium exchange could make this technique more routine for structural elucidation. Open port sampling interface mass spectrometry (OPSI‐MS) with an aprotic solvent offers a rapid method for performing deuterium incorporation. Methods: Samples of standard drug molecules have been analysed by OPSI‐MS directly from solids using a make‐up flow of acetonitrile + 0.1% trifluoroacetic acid. The resultant spectra were compared with those obtained by OPSI‐MS analysis of the samples dissolved in deuterium oxide (D2 O). Solutions of these molecules in acetonitrile/D2 O were analysed using an Atmospheric Solids Analysis Probe (ASAP) at different temperatures to compare the suitability of this technique. Results: The number of exchangeable hydrogens was obtained through deuterium exchange using the OPSI source, although there was some incomplete exchange or back‐exchange observed. Molecules with one to five exchangeable hydrogens were successfully analysed. ASAP analysis produced more complicated spectra with higher levels of incomplete or back‐exchanged ions; this was more pronounced at higher temperatures. Conclusions: The use of OPSI provides a method for the rapid determination of the number of exchangeable hydrogens within a molecule. This yields useful information as an aid to the structural elucidation of unknowns. ASAP produces incomplete exchange and cannot be used for incorporation studies.